PENYELENGGARAAN PROGRAM BELAJAR BARENG (BELBAR) UNTUK SISWA SD DI DESA KABAR UTARA UNTUK MENGISI AKTIVITAS SISWA PADA MASA PANDEMI - Hidayatulloh, Alpiana; Pratama, Indah Arry; Hr, BQ. Malikah; Zaidah, Alpi; Sukandi, Sukandi (Devote: Jurnal Pengabdian Masyarakat Global, 2022)
This community service aims to provide additional lessons for elementary school children. This Studying together collaborates with the youth of Syubban Syu'ada, MI NW library, and SDN 1 Kabar. The methods used in this program are speech, learning while playing, group work methods, etc. The target to be achieved in this activity is that they fill the time at home during online learning with useful things so that children do not be left behind in understanding the material presented online. The results of this program are students understand the material as well as know some easy and fun method of learning that was not given by the school.